2019
DOI: 10.1038/s41525-019-0082-y
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-resistant B cell acute lymphoblastic leukemia displays receptor tyrosine kinase activation

Abstract: The response of childhood acute lymphoblastic leukemia (ALL) to dexamethasone predicts the long-term remission outcome. To explore the mechanisms of dexamethasone resistance in B cell ALL (B-ALL), we generated dexamethasone-resistant clones by prolonged treatment with dexamethasone. Using RNA-sequencing and high-throughput screening, we found that dexamethasone-resistant cells are dependent on receptor tyrosine kinases. Further analysis with phosphokinase arrays showed that the type III receptor tyrosine kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…Notably, the analyses with primary B-ALL samples in our study, which revealed a potent induction of NK cell ADCC by 4G8-SDIE, included several CD20 negative cases. This provides further evidence for the value of FLT3 targeting in B-ALL, in particular since other investigators implicated FLT3 to be expressed on leukemic stem cells in ALL [32] and that FLT3 may associate with B-ALL cell resistance to conventional therapy [33]. Heterogeneous expression of FLT3 on the mRNA level and on the cell surface in B-ALL patients has been reported by other investigators [34][35][36], and a trend for a correlation of low FLT3 expression and relapse was observed in an Indian cohort of ALL patients, without reaching statistical significance [34].…”
Section: Discussionsupporting
confidence: 53%
“…Notably, the analyses with primary B-ALL samples in our study, which revealed a potent induction of NK cell ADCC by 4G8-SDIE, included several CD20 negative cases. This provides further evidence for the value of FLT3 targeting in B-ALL, in particular since other investigators implicated FLT3 to be expressed on leukemic stem cells in ALL [32] and that FLT3 may associate with B-ALL cell resistance to conventional therapy [33]. Heterogeneous expression of FLT3 on the mRNA level and on the cell surface in B-ALL patients has been reported by other investigators [34][35][36], and a trend for a correlation of low FLT3 expression and relapse was observed in an Indian cohort of ALL patients, without reaching statistical significance [34].…”
Section: Discussionsupporting
confidence: 53%
“…5f ) were downregulated in TANOUE cells. Although we observed that FLT3 expression was downregulated in predicted dexamethasone-resistant ALL patient samples, in vitro development of dexamethasone resistance in cell lines using long-term culture retained FLT3 expression in resistant cells and even selected for oncogenic FLT3 mutations 5 . Therefore, it is likely that the loss of FLT3 expression occurs in a portion of ALL patients and might not be a common feature for all dexamethasone-resistant ALL samples.…”
Section: Resultsmentioning
confidence: 55%
“…To understand why the model failed to detect two samples as resistant, we analyzed the gene expression data (FPKM) from those samples. In this dataset, three sensitive cell lines (697, NALM6, and RS4;11) were treated with dexamethasone to generate dexamethasone-resistant cell lines 5 . The resistant cell line TANOUE was used as a control and was also treated with dexamethasone for the same period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, glucocorticoids (GCs), such as prednisone and dexamethasone, in combination with conventional chemotherapeutic agents such as cytarabine, etoposide, or daunorubicin are used to treat infant ALL. Although GC is a key agent for targeting lymphoid malignancies, basic experimental studies showed that MLL-ALL cells become rapidly resistant to GCs in vitro [ [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] ] an in vivo [ 3 , 18 , 20 , 21 ]. Therefore, it is important to develop new drugs that can recognize the abnormal proteins, expressed by MLL-ALL cells and subsequently eliminate these.…”
Section: Introductionmentioning
confidence: 99%